Corporate Social Responsibility (CSR) Initiatives at Multinational Companies in Malaysia - Muhamad Sham Shahkat Ali (The Indonesian Journal of Communication Studies, 2008)
Today it is generally accepted that organisations have social responsibilities that extend well beyond what in the past was commonly referred to simply as the “business economic function”. This study sets out to find out the motivation of Shell Malaysia (SM) in practicing their CSR initiatives. Understanding that no metaphor is perfect and that the pyramid of CSR by Archie B Carroll is no exception, the four responsibilities: economic, legal, ethical and philanthropic is intended to portray that the total CSR of SM’s business comprising distinct components that, taken together, constitute the whole. Intensive interview was done within the sphere of SM’s Corporate Affairs (CA) Department directed to the senior management. Motivations that lead to CSR initiatives is the earning of goodwill which help SM optimise its portfolio and maintains its license to operate and grow, enhancement of reputation, retention of good employment talent, investor relations and access to capital, reduction and management of project risk through risk profile and risk management, encouragement of innovation inspired by society’s expectations, reinforcement of customer loyalty, and lastly, the gains of eco- efficiency through societal approval that increases overall business efficiency. The studied organisation practices CSR according to the four responsibilities in Carroll’s pyramid: economic, legal, ethical and philanthropic. In spite, having the ethical and philanthropic layers added only recently, SM’s CSR initiatives seemed to have gone beyond that, practicing strategic engagement into the field, which puts it in the lead compared to many organisations. Hence, imprinting a name for itself to serve as a benchmark or role model for other organisations to follow.